PENGARUH IKLAN, PERSEPSI KUALITAS, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Devita Adela V; Nurhaliza Tri Fabella; Agum Alfanis (Universitas Mitra Indonesia, 2021)
AbstractThis research is a test that aims to measure the effect of advertising, perceived quality, and brand image on consumer purchasing decisions. The number of samples in this study were 77 respondents. Sampling in this study was carried out with a cross-sectional survey design. Data collection was carried out by distributing forms (questionnaires) in the form of online statements to respondents. Statistical tests were performed using PLS-based Structural Equation Modeling. The validity test uses the loading factor value, while the reliability uses the cronbach'c alpha value, composite reliability and Average Variance Extracted (AVE). After all the indicators of the items used in this study are valid and reliable, then the hypothesis is tested. Of the three hypotheses proposed, all are supported, but for the first and third hypotheses they are not significant.Keywords : Advertising, Quality Perception, Brand Image, Purchasing Decisions